(untitled) (Italiano LinguaDue, 2020)
Il contributo considera i processi di educazione linguistica sottesi al metodo orale puro propugnato da Tarra. Tali processi saranno analizzati in relazione alle questioni più pregnanti per l’educazione linguistica scolastica del tempo. In particolare, il contributo si sofferma sulle proposte per incoraggiare l’uso della lingua italiana tra gli studenti sordomuti, sul ruolo ritagliato per i dialetti e, più in generale, sulle caratteristiche del metodo glottodidattico tarriano. The linguistic pedagogy of Giulio Tarra The contribution considers language education processes underlying the pure oral method advocated by Tarra. These processes are analyzed in relation to the most significant issues for current school language education. In particular, the contribution focuses on proposals to encourage the use of the Italian language among deaf-mute students, on the role of dialects and, more generally, on the characteristics of Tarra’s language teaching methodology.